The human right to water : legal and policy dimensions - Salman, Salman M. A.; McInerney-Lankford, Siobhán Alice (Washington, D.C. : World Bank, 2004)
Traces the issue of the right to water through a number of international legal instruments, particularly General Comment No. 15, issued in 2002 by the Committee on Economic, Social and Cultural Rights, which recognizes a human right to water. It analyzes the international legal regime for human rights and argues that the development-water-human rights nexus is rapidly evolving.
Includes bibliographical references (p. [91]-98) and index.
oif 01/04/15; 20/08/15; ijb 03/04/2019
Loans
Keywords: Water rights; Human rights; Right to water